Distant Temporal Distance and Creative Thinking: The Mediating Role of Promotion Motivation - Chen, Peipei; Zhang, Jinghuan; Qi, Yiliang (Frontiers in Psychology, 2020)
Abstract: The present study examined the effect of distant temporal distance on creative thinking and the underlying motivation mechanism. We tested our hypotheses in four studies. In Studies 1-4, participants in the distant temporal distance opposed to the proximal temporal distance performed better on a series of creative thinking tasks: the Alternate Uses Task (Study 1), the Chinese Remote Associates Test (Study 2), the Toy Design Task (Study 3) and the Ad Evaluation Task (Study 4). Moreover, Studies 2 and 3 found that promotion motivation mediated the beneficial effect of distant temporal distance on the performance of the two creative thinking tasks. In conclusion, distant temporal distance facilitated creative thinking, and promotion motivation mediated this beneficial effect.